A study on price oriented promotions effects on brand loyalty - Janette, Boniface Barau (Universiti Malaysia Sarawak (UNIMAS), 2012)
rice-oriented sales promotion techniques are important in marketing activities as part of the strategy to increase sales and profit either in short or long term. Nevertheless, maintaining or enhancing brand loyalty is essential to promote brands' advantage. Therefore, this study aims to examine the effects of price-oriented promotions on brand 10yalti)The objective of this study is to investigate the influence of predisposition to use price sales promotional tools in buying other than preferred brand products would effects his or her brand loyalty level among personal care product users or buyers. Questionnaires were distributed and self-administered to 150 respondents. Descriptive analysis, One-way ANOVA, independent t-test, Pearson correlation and simple regression analysis were used in this study. This study strived to determine the differences of predisposition to use price-oriented promotional tools towards consumer's brand loyalty. The fmdings of this study indicated that 'consumers have strong correlation with brand loyalty. In addition, this research would give managerial implications for marketers with regards to customer preferences to improve their strategy in enhancing product brand name.